PREVALENSI DAN FAKTOR YANG BERHUBUNGAN DENGAN SKABIES DI PONDOK PESANTREN AL ANSHOR KOTA AMBON - Azzahra, Fatimah; Manuputty, Amanda Gracia; Silalahi, Parningotan Yosi (Fakultas Kedokteran Universitas Pattimura, 2024)
Scabies is a contagious skin disease caused by a parasitic infestation of the tiny mite Sarcoptes scabiei var hominis in many tropical countries including Indonesia. It is estimated 300 million cases of scabies each year in the world. It can have a significant impact on general health, causing illness and death not only as a direct result of its infestation but also as a result of secondary bacterial infection. To analyze the associated factors of scabies in Boarding School Al Anshor, Ambon in 2022. This study used an observational analytic research method with cross-sectional design. Based on the results of the doctor's diagnosis, 68 students (31.78%) suffered from scabies. Female students dominate scabies sufferers. In addition, it was also found that scabies mostly occurred in students with the age of 15 years. Scabies is dominated by students with a high school education level as many as 41 students. It was found that the factors of gender (p=0,755), age (p=0,089), and education level of students (p=0,074) had no statistical effect on the prevalence of scabies in the Al Anshor boarding school in Ambon. It can be concluded that there is no relationship between gender, age, and education level and scabies.